EXISTENCE AND SINGULARITY WITH FRACTIONAL DERIVATIVES FOR THE TELEGRAPH EQUATION. - T. R. Suyarov (Лучшие интеллектуальные исследования, 2024)
Abstracts. In this paper, we present an analytical method for solving the fractional telegraph problem corresponding to the fractional time derivative. Many physical processes are represented by a system of first and second order hyperbolic type equations. Telegraph equation of electromagnetic oscillations, dynamic equations of elasticity theory and others. So that second-order equations are derived from them by means of a number of additional constraints.